Effect of physical Activity on menstrual cycle in adolescence - رجب, رجاء (Latakia University Journal -Medical Sciences Series, 2023)
Background: Regular physical activity helps to prevent heart disease, stroke and diabetes. Also, to prevent high blood pressure, maintain a healthy body weight, and can improve mental health and quality of life. Globally, 81% of adolescents aged 11-17 years were not sufficiently physically active in 2016. Many studies have proven that physical activity and exercise have a significant effect in reducing menstrual irregularities. METHODS: A cross-sectional study of 164 adolescent girls questioned about menstrual cycle characteristics, age, marital status, weight, height, puberty, smoking, physical activity. We studied the effect of physical activity on each parameter of the menstrual cycle individually and then with the participation of other factors such as age, smoking, weight, puberty, and family status of the participant. Results: The ages of the participants ranged between 13 and 21 years (1.8 ± 19). 25% were smokers. 17.7% were overweight. And 5.5% were obese. 41.5% suffered from irregular menstrual cycle. 4.3% suffered from oligomenorrhea. 3.6% of polymenorrhagia. 26.8% suffered from menorrhagia, 21.9% s from metrorrhagia. 45.7% of dysmenorrhea. 79.3% of the participants do not practice any physical activity outside of daily activities, 20.7% engage in physical activity (at least walking). In our study, we found that lack of physical activity affects the parameters of the menstrual cycle, as it increases the risk of menorrhagia, metrorrhagia, and dysmenorrhea (p value 0.005, <0.001, 0.002, respectively) independently of the weight of the adolescent. Conclusion: Lack of physical activity in adolescent girls is a risk factor for menstrual disorders.